Electricity Consumption in the Green Transition of Steelmaking: A Case Study of OHF/BF vs. Midrex-EAF at Zaporizhstal - Kukhar, V. V.; Tymoshenko, D. O.; Volovnenko, I. V.; Kurpe, O. H.; Pashynskyi, V. V.; Shaulska, L. V.; Кухар, В. В.; Тимошенко, Д. О.; Воловненко, І. В.; Курпе, О. Г.; Пашинський, В. В.; Шаульська, Л. В. (IEEE, 2025)
The paper emphasizes the urgent need for Ukraine's metallurgy sector, particularly at PJSC "Zaporizhstal," to replace outdated technologies with modern, sustainable steel production methods as part of a global "green transition". The investigation encompassed field measurements, followed by rigorous data processing and analysis. A comparative analysis was conducted to enhance the findings. The study compares the electricity consumption at two different steel production methods: (I) iron ore sintering process (IOSP) with an aspiration system + blast furnace (BF) + an open-hearth furnace (OHF) smelting; (II) Midrex process + electric arc furnaces (EAF) smelting. The analysis revealed that the specific energy consumption (SEC) varies significantly across different processes: the Electric Arc Furnace (EAF) requires the highest at approximately 340 kWh/t, followed by the Midrex process at 85 kWh/t. The Open Hearth Furnace (OHF) and Blast Furnace (BF) show lower energy demands at around 4 kWh/t and 3.3 kWh/t respectively, while the Sintering Plant (SP) consumes about 33 kWh/t. It is evident that the "IOSP + BF + OHF" method generates substantially higher CO2 emissions than the more efficient "Midrex + EAF" approach. The IOSP is among the most energy-intensive processes, whereas the BF requires less energy. The OHF, though consuming relatively little energy, is less attractive due to its inefficiency. While the Midrex process demands more energy than traditional methods, it compensates with substantial environmental advantages by emitting less CO2. The Electric Arc Furnace (EAF), despite its high energy requirements, excels in the efficient and flexible recycling of steel scrap. Research indicates that adopting advanced technologies like Direct Reduction (DR) via the Midrex process, followed by pellet melting in an EAF, is a crucial step toward lowering emissions and enhancing the energy efficiency of modern steelmaking practices.

У роботі наголошено на нагальній потребі металургійного сектору України, зокрема на ПАТ «Запоріжсталь», у заміні застарілих технологій сучасними сталими методами виробництва сталі в межах глобального «зеленого переходу». Дослідження охоплювало натурні вимірювання з подальшою ретельною обробкою та аналізом даних. Для підвищення обґрунтованості результатів було проведено порівняльний аналіз. У роботі порівнюється споживання електроенергії за двома різними методами виробництва сталі: (I) процес агломерації залізної руди (IOSP) з аспіраційною системою + доменна піч (BF) + мартенівська піч (OHF); (II) процес Midrex + плавка в електродугових печах (EAF). Аналіз показав, що питоме енергоспоживання (SEC) істотно відрізняється для різних процесів: електродугова піч (EAF) має найбільше значення — приблизно 340 кВт·год/т, далі йде процес Midrex — 85 кВт·год/т. Мартенівська піч (OHF) та доменна піч (BF) характеризуються нижчим енергоспоживанням — близько 4 кВт·год/т і 3,3 кВт·год/т відповідно, тоді як агломераційна фабрика (SP) споживає близько 33 кВт·год/т. Очевидно, що метод «IOSP + BF + OHF» генерує суттєво вищі викиди CO₂ порівняно з більш ефективним підходом «Midrex + EAF». Процес IOSP належить до найбільш енергоємних, тоді як доменна піч потребує меншої кількості енергії. Мартенівська піч, незважаючи на відносно низьке енергоспоживання, є менш привабливою через свою низьку ефективність. Хоча процес Midrex потребує більше енергії, ніж традиційні методи, він компенсує це суттєвими екологічними перевагами, зокрема нижчими викидами CO₂. Електродугова піч (EAF), попри високі енергетичні витрати, відзначається ефективною та гнучкою переробкою сталевого брухту. Результати досліджень свідчать, що впровадження передових технологій, таких як пряме відновлення (DR) за процесом Midrex з подальшим плавленням окатишів в EAF, є ключовим кроком до зниження викидів і підвищення енергоефективності сучасного сталеплавильного виробництва.
Keywords: energy consumption; electricity; green products; smelting; sintering; production; air pollution; energy efficiency; metallurgy; steel; green transition in metallurgy; steelmaking methods; specific energy consumption; CO2 emissions; energy efficiency; midrex process; electric arc furnaces; споживання енергії; електроенергія; зелена продукція; плавка; агломерація; виробництво; забруднення повітря; енергоефективність; металургія; сталь; зелений перехід у металургії; методи сталеплавильного виробництва; питоме енергоспоживання; викиди CO₂; енергоефективність; процес midrex; електродугові печі